EKSISTENSI LEGENDA ORANG KAYO HITAM DI JAMBI - Febrianti, Maya; Anwar, Khairil; Zurmailis, Zurmailis (Universitas Andalas, 2023)
The legend of the Orang Kayo Hitam is a folk tale from Jambi. The legend of the Orang Kayo Hitam develops between spoken and written. The legend of the Orang Kayo Hitam is considered a historical story or folklore that has meaningful values in life. This paper will discuss the existence of the Legend of the Orang Kayo Hitam in Jambi with the aim of describing the existence of the Legend of the Orang Kayo Hitam in society and the existence of the Legend of the Orang Kayo Hitam in literary works. The research method is a qualitative descriptive method using explanations. Data analysis was done by rereading interview data and story books to get results that are close to the problem formulation. The result of this paper is the existence of the Legend of the Orang Kayo Hitam seen from the community, the author continues to work by himself by the Legend of the Orang Kayo Hitam. For the people of the Legend of the Orang Kayo Hitam, it is very influential in social life, besides that people easily tell briefly the Legend of the Orang Kayo Hitam, some relics of the Orang Kayo Hitam are still used as icons in Jambi. While in literary works, the author describes the Legend of Orang Kayo Hitam fairly, the work used in this paper has a long period of publication and has differences in the title and content of the story text. The message conveyed was that Jambi had a firm leader during his reign, Orang Kayo Hitam had an influence in the creation of new works.